2022
DOI: 10.1038/s41467-022-31401-5
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex-specific risks of myocarditis and pericarditis following Covid-19 messenger RNA vaccines

Abstract: Cases of myocarditis and pericarditis have been reported following the receipt of Covid-19 mRNA vaccines. As vaccination campaigns are still to be extended, we aimed to provide a comprehensive assessment of the association, by vaccine and across sex and age groups. Using nationwide hospital discharge and vaccine data, we analysed all 1612 cases of myocarditis and 1613 cases of pericarditis that occurred in France in the period from May 12, 2021 to October 31, 2021. We perform matched case-control studies and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 31 publications
5
63
0
Order By: Relevance
“…Extending our previous study, 6 we conducted a matched case-control study within the entire French population aged 12 or older, from December, 27, 2020 to January, 31, 2022. We included all 4,890 cases of myocarditis admitted to French hospitals along with 48,900 controls of the general population matched for gender, age, and area of residency.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Extending our previous study, 6 we conducted a matched case-control study within the entire French population aged 12 or older, from December, 27, 2020 to January, 31, 2022. We included all 4,890 cases of myocarditis admitted to French hospitals along with 48,900 controls of the general population matched for gender, age, and area of residency.…”
Section: Main Textmentioning
confidence: 99%
“…Extending our previous study 1 , we conducted a matched case-control study within the entire French population aged 12 or older, from the beginning of the Covid-19 vaccination campaign in December, 27, 2020 to January, 31, 2022.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, two studies reported that COVID-19 mRNA vaccine-induced myocarditis disproportionately affected adolescents (reporting odds ratio (ROR): 22.3; 95% confidence interval (CI): 19.2-25.9), 18-29-year-olds (ROR: 6.6; 95% CI: 5.9-7.5), and males (ROR: 9.4; 95% CI: 8.3-10.6) [ 5 , 6 ]. These findings were supported by another large registry study that identified increased myocarditis risk following SARS-CoV-2 mRNA vaccination, with the highest risk detected in people aged 18-24 years, particularly after the second dose, where 8.1-fold increased risk after the BNT162b2 SARS-CoV-2 mRNA vaccine (95% CI: 6.7-9.9) and 30-fold increased risk after the mRNA-1273 SARS-CoV-2 vaccine (95% CI: 21-43) were reported [ 7 ]. An Israeli government dataset demonstrated 13.6-fold increased myocarditis risk (95% CI: 9.3-19.2) among males aged between 16 and 19 years compared to the expected following historical data, while a ninefold increased myocarditis risk (95% CI: 4.5-17.8) was recorded when compared to unvaccinated people of similar age and sex during the same period [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Not only were myocarditis risks identified, but a great burden following these cardiac events was also described [ 7 ]. Indeed, young males with comorbidities may experience dramatic cardiac remodeling following SARS-CoV-2 mRNA vaccination [ 11 ].…”
Section: Introductionmentioning
confidence: 99%